Quantitative statistical method for nano precipitated phase in biphase strengthened Al-Zn-Mg-Cu aluminum alloy

Through transmission electron microscopy morphology image statistics, and combining the crystal direction relationship to calculate the proportion of T′ phase and η′ phase, the quantitative statistical problem of precipitation phase in Al-Zn-Mg-Cu aluminum alloy is solved, and efficient and simple mechanics are achieved Performance research support.

CN119290925APending Publication Date: 2025-01-10CHONGQING TECH & BUSINESS UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411431075.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

It is difficult for the prior art to accurately count the number and proportion of T′ phase and η′ phase in Al-Zn-Mg-Cu aluminum alloy, resulting in limited research on mechanical properties. The traditional method has small analysis area, cumbersome process and low testing efficiency.

Method used

Through transmission electron microscope morphology images, the number of circular/elliptical and rectangular precipitation phases are counted, and the number and proportions of T′ phases and η′ phases are calculated based on the observation direction and the crystal direction relationship of the aluminum alloy.

Benefits of technology

The efficient, simple and fast quantitative statistics of nano-precipitation phases in two-phase reinforced Al-Zn-Mg-Cu aluminum alloy are achieved, solving the problems of small areas and cumbersome processes of traditional methods, and providing technical support for the study of mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119290925A_ABST
    Figure CN119290925A_ABST
Patent Text Reader

Abstract

The invention discloses a quantitative statistical method for a nano precipitated phase in a biphase strengthened Al-Zn-Mg-Cu aluminum alloy, which comprises the following steps: S1, carrying out transmission electron microscope characterization on a sample of the biphase strengthened Al-Zn-Mg-Cu aluminum alloy to obtain an observation direction and the lt of the aluminum alloy; 110gt, 110gt; or lt; 112gt, 112gt; a precipitated phase distribution image when crystal orientations are parallel; s2, counting the precipitated phase distribution image, and counting the number B of circular / elliptical precipitated phases and the number A of rectangular precipitated phases; and S3, selecting a corresponding precipitated phase number calculation model based on the observation direction, substituting the number B and the number A counted in the step S2 into the precipitated phase number calculation model, and calculating the number and the proportion of the T'phase and the eta 'phase. The method can solve the problems of small analysis area, tedious characterization process, low test efficiency and the like of the traditional characterization method of the nano precipitated phase in the aluminum alloy, and has the advantages of high efficiency, simplicity, convenience and rapidness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quantitative characterization of material microstructure, and in particular to a quantitative statistical method for nano-precipitated phases in a dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy. Background Art

[0002] Aluminum alloy has the advantages of light weight, high strength, good corrosion resistance and good formability, and is the non-ferrous metal with the highest output. Al-Zn-Mg-Cu aluminum alloy is the aluminum alloy with the highest strength and is an ideal weight-reducing material. It is widely used in aerospace, transportation and other fields. The high strength of Al-Zn-Mg-Cu aluminum alloy comes from the nano-sized precipitation phase formed during the aging process. T′ phase and η′ phase are the main precipitation phases formed during the aging process of Al-Zn-Mg-Cu aluminum alloy. These two precipitation phases are the key factors affecting the mechanical properties of the alloy. However, T′ phase and η′ phase have different crystal structures and morphologies, and different strengthening models are usually used to evaluate their effects on strength. Therefore, accurately counting the number and proportion of T′ phase and η′ phase in Al-Zn-Mg-Cu aluminum alloy is a necessary prerequisite for quantitative characterization of the two, which is of great significance for the study of the mechanical properties of dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy.

[0003] The characterization of nano-precipitated phases in Al-Zn-Mg-Cu aluminum alloys is usually carried out using transmission electron microscopy, and the images captured by transmission electron microscopy are two-dimensional projection morphologies of the precipitated phases. The T′ phase in the nano-precipitated phase is spherical / ellipsoidal, and the projection morphology observed from any direction is circular / elliptical. The η′ phase is disc-shaped and precipitates on the (111) surface of the aluminum matrix. Since there are four equivalent (111) surfaces in the aluminum matrix, and the probability of η′ phase precipitation on each (111) surface is equal, the projection morphology of η′ phase will appear circular / elliptical and rectangular when observed from different directions. Therefore, it is impossible to distinguish between T′ phase and η′ phase in the images obtained from the transmission electron microscope, resulting in the inability to count their number and proportion. Although the type of precipitated phase can be determined by collecting high-resolution images of the precipitated phase and obtaining the corresponding fast Fourier transform pattern through image processing, the field of view of the high-resolution image is very limited, and the shooting requirements for the sample thickness are high. Therefore, sample preparation and statistics of precipitated phases in a large range are very cumbersome and labor-intensive. The quantitative statistical characterization of T′ phase and η′ phase in a large size range becomes a major difficulty.

[0004] Therefore, it is necessary to develop an efficient, simple and fast statistical method for the number of T′ phase and η′ phase in dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy, so as to provide technical support for comprehensive analysis of the influence mechanism of precipitation phase on the mechanical properties of Al-Zn-Mg-Cu aluminum alloy and precise regulation of microstructure. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a quantitative statistical method for nano-precipitated phases in dual-phase strengthened Al-Zn-Mg-Cu aluminum alloys, which can quantitatively count the number and proportion of T′ phase and η′ phase in dual-phase strengthened Al-Zn-Mg-Cu aluminum alloys only through ordinary transmission electron microscope morphology images.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention discloses a quantitative statistical method for nano-precipitated phases in a dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy, comprising the following steps:

[0008] S1, transmission electron microscopy characterization of the dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy samples to obtain the observation direction and aluminum alloy <110> or <112> Distribution image of precipitated phase when the crystal directions are parallel;

[0009] S2, counting the precipitate phase distribution image, and counting the number B of circular / elliptical precipitates and the number A of rectangular precipitates;

[0010] S3, selecting a corresponding precipitate phase quantity calculation model based on the observation direction, substituting the quantity B and quantity A counted in step S2 into the precipitate phase quantity calculation model, and calculating the quantity and ratio of the T′ phase and the η′ phase;

[0011] When the viewing direction is the same as that of the aluminum alloy <110> When the crystal directions are parallel, the calculation model for the number of precipitated phases is: the number of η′ phases = 2A, the number of T′ phases = BA;

[0012] When the viewing direction is the same as that of the aluminum alloy <112> When the crystal directions are parallel, the calculation model for the amount of precipitated phase is: the amount of η′ phase = 4A, the amount of T′ phase = B-3A.

[0013] As a preferred technical solution, in step S1, the sample is a transmission electron microscope sample with holes and surrounding thin areas, and any thin area position is selected as the observation area.

[0014] As a preferred technical solution, in step S1, multiple precipitation phase distribution images of the sample in different observation areas are obtained; in step S3, the number and proportion of precipitation phases in different observation areas are obtained, and their average values ​​are calculated to reduce the error caused by different observation areas.

[0015] The beneficial effects of the present invention are:

[0016] The present invention can quantitatively count the number and proportion of T' phase and η' phase in the dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy only through ordinary transmission electron microscope morphology images, without further high-resolution imaging and selected area electron diffraction technology to determine the types of different precipitated phases. The present invention can solve the problems of small analysis area, cumbersome characterization process, low test efficiency, etc. of the traditional nano-precipitate phase characterization method in aluminum alloy, and has the advantages of high efficiency, simplicity and rapidity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0018] Figure 1 a is the crystallographic orientation relationship between the η′ phase and the aluminum matrix;

[0019] Figure 1 b is η′ <110> Projection morphology of crystal orientation;

[0020] Figure 2 a is the crystallographic orientation relationship between the η′ phase and the aluminum matrix;

[0021] Figure 2 b is η′ <112> Projection morphology of crystal orientation;

[0022] Figure 3 a is the crystallographic orientation relationship between the T′ phase and the aluminum matrix;

[0023] Figure 3 b is T' phase <110> Projection morphology of crystal orientation;

[0024] Figure 3 c is T' phase <112> Projection morphology of crystal orientation;

[0025] Figure 4 The alloy to be tested in Example 1 is <110> Transmission electron microscope image of the precipitate phase distribution obtained by crystal orientation;

[0026] Figure 5 The alloy to be tested in Example 1 is <112> Transmission electron microscope image of the precipitate phase distribution obtained by crystal orientation. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0028] The present invention found that the morphology of the η′ phase in the Al-Zn-Mg-Cu aluminum alloy is disk-shaped, and the η′ phase precipitates on the (111) crystal plane of the aluminum matrix. Its distribution model is as follows: Figure 1a. Therefore, when the observation direction is the aluminum alloy <110> When the crystal direction is Figure 1 As shown in b, the projection morphology of the η′ phase is rectangular and circular / elliptical, and the ratio of the two is 1:1. <112> When the crystal direction is Figure 2 As shown in Fig. b, the projected morphology of the η′ phase is still rectangular and circular / elliptical, but the ratio of the two is 1:3. The morphology of the T′ phase in the Al-Zn-Mg-Cu aluminum alloy is spherical ( Figure 3 a), so when the observation direction is the aluminum alloy <110> and <112> When the crystal direction is oriented, the projection morphology of the T′ phase is circular ( Figure 3 b and Figure 3 c).

[0029] Therefore, based on the above precipitated phase morphology and its proportional relationship when observed in different crystal directions, a precipitated phase quantity calculation model can be established (as shown in Table 1):

[0030] The number of rectangular precipitates A and the number of circular / elliptical precipitates B in the image are obtained by statistics; the precipitates with rectangular morphology must be η′ phase, while the precipitates with circular / elliptical morphology contain both η′ phase and T′ phase. Figure 1-3 From the established model, it can be seen that when the observation direction is <110> When the crystal direction is , the ratio of rectangle to circle / ellipse in the projection morphology of η′ phase is 1:1, so the amount of η′ phase in the precipitated phase with circular / ellipse morphology is also A. Therefore, the amount of η′ phase in the image is A+A=2A, and the amount of T′ phase is BA. Similarly, when the observation direction is <112> In the crystal direction, the ratio of rectangle to circle / ellipse in the projected morphology of η′ phase is 1:3, so the amount of η′ phase in the precipitated phase with circular / elliptical morphology is 3A. It can be obtained that the amount of η′ phase in the image is A+3A=4A, and the amount of T′ phase is B-3A.

[0031] Table 1. Quantity calculation model of η′ phase and T′ phase in Al-Zn-Mg-Cu aluminum alloy samples

[0032] Model Observation direction Number of rectangles Number of circles / ovals η′ phase quantity T' phase quantity Model 1 <110> A B 2A BA Model 2 <112> A B 4A B-3A

[0033] Based on the above findings, the present invention designs a quantitative statistical method for nano-precipitated phases in dual-phase strengthened Al-Zn-Mg-Cu aluminum alloys, comprising the following steps:

[0034] S1, transmission electron microscopy characterization of the dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy samples to obtain the observation direction and aluminum alloy <110> or <112> Distribution image of precipitated phase when the crystal directions are parallel;

[0035] S2, counting the precipitate phase distribution image, and counting the number B of circular / elliptical precipitates and the number A of rectangular precipitates;

[0036] S3, selecting a corresponding precipitate phase quantity calculation model based on the observation direction, substituting the quantity B and quantity A counted in step S2 into the precipitate phase quantity calculation model, and calculating the quantity and ratio of the T′ phase and the η′ phase;

[0037] When the viewing direction is the same as that of the aluminum alloy <110> When the crystal directions are parallel, the calculation model for the number of precipitated phases is: the number of η′ phases = 2A, the number of T′ phases = BA;

[0038] When the viewing direction is the same as that of the aluminum alloy <112> When the crystal directions are parallel, the calculation model for the amount of precipitated phase is: the amount of η′ phase = 4A, the amount of T′ phase = B-3A.

[0039] Example 1

[0040] The aluminum alloy sample used in this embodiment is an Al-Zn-Mg-Cu aluminum alloy that is die-cast and then solution treated and aged. The main alloy element contents determined by direct reading spectroscopy (OES) are shown in Table 2.

[0041] Table 2. Main alloying element contents of Al-Zn-Mg-Cu aluminum alloy samples (wt%)

[0042] element Zn Mg Cu Si Fe content 6.00 2.71 0.94 0.037 0.086

[0043] Based on the Al-Zn-Mg-Cu aluminum alloy sample, quantitative statistics of nano-precipitated phases are performed, including the following steps:

[0044] Step 1: Obtain a transmission electron microscope image of the precipitate phase distribution.

[0045] A 0.5mm thick sheet sample was taken from the bulk alloy sample by wire cutting, and the sheet sample was mechanically thinned to 70μm thick using 400-3000 mesh silicon carbide sandpaper, and the 70μm thick alloy sample was cut into a 3mm diameter disc sample using a special transmission electron microscope puncher. The disc sample with a diameter of 3mm and a thickness of 70μm was prepared into a standard transmission electron microscope sample with a hole in the center and a thin area near the hole by the electrolytic double spray method, wherein the electrolyte was composed of 25% nitric acid and 75% methanol, the working temperature was <-30℃, the working voltage was 10-15V, and the current was 50-100mA.

[0046] Subsequently, a transmission electron microscope was used to characterize the precipitated phase particles in the alloy sample to be tested. The working voltage of the transmission electron microscope was 200 kV, and the observation direction was adjusted by tilting the angle of the transmission electron microscope sample stage so that the observation direction was consistent with the aluminum alloy. <110> or <112> The built-in camera of the transmission electron microscope was used to photograph the distribution of the precipitated phase particles in the observed area, and the <110> and <112> The distribution image of the precipitated phase observed in the direction, such as Figure 4 and Figure 5 shown.

[0047] Step 2: Obtain the number of precipitated phases with different morphologies based on the transmission electron microscope image.

[0048] The distribution image of the precipitation phase of Al-Zn-Mg-Cu aluminum alloy is as follows Figure 4 and Figure 5 As shown, Figure 4 and Figure 5 There are mainly two types of precipitated phases in the morphology: rectangular and circular / elliptical. After statistics, the number of precipitated phases with the two morphologies is shown in Table 3.

[0049] Table 3. Number of precipitates with different morphologies in Al-Zn-Mg-Cu aluminum alloy samples

[0050] Rectangular precipitate phase A Round / elliptical precipitate phase B Total number of precipitated phases <110> 17 181 198 <112> 5 114 119

[0051] Step 3: Select the corresponding precipitated phase quantity calculation model based on the observation direction, and calculate the quantity and proportion of T′ phase and η′ phase.

[0052] When the viewing direction is the same as that of the aluminum alloy <110> When the crystal directions are parallel, the calculation model for the number of precipitated phases is: the number of η′ phases = 2A, the number of T′ phases = BA. The number of rectangular precipitated phases A = 17, the number of circular / elliptical precipitated phases B = 181, so the number of η′ phases is calculated to be 17+17=34, the number of T′ phases is 181-17=164, and the ratio between the two is 1:4.82.

[0053] When the viewing direction is the same as that of the aluminum alloy <112> When the crystal directions are parallel, the calculation model for the number of precipitated phases is: the number of η′ phases = 4A, the number of T′ phases = B-3A. The number of rectangular precipitated phases A = 5, and the number of circular / elliptical precipitated phases B = 119. Therefore, the number of η′ phases is calculated to be 5+3×5=20, and the number of T′ phases is 114-3×5=99, and the ratio between the two is 1:4.95.

[0054] According to the above calculation results, it can be seen that the proportions of precipitated phases calculated using different models are very close.

[0055] Preferably, multiple precipitated phase distribution images of the sample in different observation areas can be obtained to obtain the quantity and proportion of precipitated phases in different observation areas, and the average value thereof is calculated to reduce the error caused by different observation areas.

[0056] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A quantitative statistical method for nano-precipitated phases in dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy, characterized in that: The following steps are involved: S1, transmission electron microscopy characterization of the dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy samples to obtain the observation direction and aluminum alloy <110> or <112> Distribution image of precipitated phase when the crystal directions are parallel; S2, counting the precipitate phase distribution image, and counting the number B of circular / elliptical precipitates and the number A of rectangular precipitates; S3, selecting a corresponding precipitate phase quantity calculation model based on the observation direction, substituting the quantity B and quantity A counted in step S2 into the precipitate phase quantity calculation model, and calculating the quantity and ratio of the T′ phase and the η′ phase; When the viewing direction is the same as that of the aluminum alloy <110> When the crystal directions are parallel, the calculation model for the number of precipitated phases is: the number of η′ phases = 2A, the number of T′ phases = BA; When the viewing direction is the same as that of the aluminum alloy <112> When the crystal directions are parallel, the calculation model for the amount of precipitated phase is: the amount of η′ phase = 4A, the amount of T′ phase = B-3A.

2. The quantitative statistical method for nano-precipitated phase in dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy according to claim 1, characterized in that: In step S1, the sample is a transmission electron microscope sample with a hole and a surrounding thin area, and any thin area position is selected as the observation area.

3. The quantitative statistical method for nano-precipitated phase in dual-phase strengthened Al-Zn-Mg-Cu aluminum alloy according to claim 2, characterized in that: In step S1, a plurality of precipitated phase distribution images of the sample in different observation areas are obtained; in step S3, the number and proportion of precipitated phases in different observation areas are obtained, and their average values ​​are calculated to reduce the error caused by different observation areas.